2017
DOI: 10.3389/fmicb.2017.00965
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Composition and Diversity in Breast Milk Samples from Mothers Living in Taiwan and Mainland China

Abstract: Human breast milk is widely recognized as the best source of nutrients for healthy growth and development of infants; it contains a diverse microbiota. Here, we characterized the diversity of the microbiota in the breast milk of East Asian women and assessed whether delivery mode influenced the microbiota in the milk of healthy breast-feeding mothers. We profiled the microbiota in breast milk samples collected from 133 healthy mothers in Taiwan and in six regions of mainland China (Central, East, North, Northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
133
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(161 citation statements)
references
References 56 publications
20
133
3
5
Order By: Relevance
“…While the average abundance of these four microbes are similar across all samples, two clusters each were characterized by higher abundances of Streptococcus and Staphylococcus, or Pseudomonas and Acinetobacter with differences in alpha diversity and the abundances of numerous other taxa further differentiating these clusters. The clusters we identified share both similarities and differences with the breast milk microbiome clusters identified in Chinese (Li et al, 2017), Italian (Biagi et al, 2018), and Canadian (Moossavi et al, 2019b) mothers, suggesting that some patterns of microbial populations in human milk may be similar amongst geographically and racially distinct populations. Bacteria belonging to the genera Acinetobacter and Pseudomonas are often thought of as pathogens contributing to nosocomial infections (Fazeli et al, 2012;Custovic et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…While the average abundance of these four microbes are similar across all samples, two clusters each were characterized by higher abundances of Streptococcus and Staphylococcus, or Pseudomonas and Acinetobacter with differences in alpha diversity and the abundances of numerous other taxa further differentiating these clusters. The clusters we identified share both similarities and differences with the breast milk microbiome clusters identified in Chinese (Li et al, 2017), Italian (Biagi et al, 2018), and Canadian (Moossavi et al, 2019b) mothers, suggesting that some patterns of microbial populations in human milk may be similar amongst geographically and racially distinct populations. Bacteria belonging to the genera Acinetobacter and Pseudomonas are often thought of as pathogens contributing to nosocomial infections (Fazeli et al, 2012;Custovic et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…Preliminary small studies using 16S rRNA gene sequencing and metagenomics approaches to assess breast milk microbial composition have reported that Streptococcus, Staphylococcus, Pseudomonas, Bacteroides, Acinetobacter, and others comprise the core breast milk microbiome, whereas Bifidobacterium and Lactobacillus abundances are comparatively low (Hunt et al, 2011;Jost et al, 2013;Ward et al, 2013;Jiménez et al, 2015;Sakwinska et al, 2016;Urbaniak et al, 2016;Murphy et al, 2017). Clusters of breast milk microbiota have been reported, often defined by the abundance of Staphylococcus, Streptococcus, and Pseudomonas, Enterobacteriaceae, and other rarer bacteria (Li et al, 2017;Biagi et al, 2018;Moossavi et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, accumulating evidence suggests that some environmental factors might influence breast milk composition (25)(26)(27). In particular, geographic location, delivery mode, maternal body mass index (BMI), and age have been suggested to have an impact on breast milk bacterial composition (28)(29)(30)(31)(32)(33)(34)(35), although their potential impact on the milk's fungal fraction is still to be elucidated.…”
mentioning
confidence: 99%
“…The second cross-cultural study supporting the notion that individual variations in breast milk bacteria may be influenced by geographic location compared milk samples collected from different regions in East Asia. 65 In this study, milk samples were compared using 454 pyrosequencing of 16 S rRNA genes between Taiwan and six-regions of mainland China. The relative abundance of Pseudomonadaceae was found to be lower in samples from Taiwan (n = 31) compared to East (n = 34), Central (n = 24) and Northeast (n = 17) China.…”
Section: Global Dietary Habits Alter Breast Milk Lipid Profile With Lmentioning
confidence: 99%